Development of The CinQASE E-Module with a Professional Flip PDF Application on Electromagnetic Induction Material To Improve The Critical Thinking Skills of Class XII Students - Hunaidah; Amiruddin Takda; Erniwati (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to create a CinQASE model e-module with Flip PDF Professional's assistance that satisfies reliable, practical, and efficient criteria. This research uses the R&D (Research and Development) method with the 4D development model (Define, Design, Develop, and Disseminate). The research subjects were 25 SMA Negeri 2 Parigi Class XII MIA A students. The instruments used are validation sheet instruments, teacher response questionnaire instruments, student responses, and critical thinking ability tests. The research shows that the CinQASE model e-module is possible with the help of the developed Flip PDF Professional app, earning a validity score of 0.83 in the very valid category. The results of the practicality of the e-module from the average teacher response were 3.84 in the very good category, and the average student response was 3.75 in the very good category. The effectiveness of students' critical thinking skills obtained an average score of 81.88 with an average n-gain of 0.78, which is included in the high category.